Socioeconomic Inequality and Access To Justice: A Comparative Analysis Of Legal Aid Systems - Valeria Huarcaya; Rafael Quispe (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This study analyzes how socioeconomic inequality affects access to justice, focusing on the effectiveness of legal aid systems in various countries. By comparing government-funded and NGO-supported legal aid programs, the article examines the barriers faced by marginalized communities in obtaining legal representation and fair trials. Results suggest that improving access to legal aid is crucial for reducing disparities in the legal system and promoting equitable justice.